A phase IIb randomized, double-blind, placebo-controlled trial of ubrogepant for the acute treatment of migraine. (August 2016) - Voss, Tiffini; Lipton, Richard B; Dodick, David W; Dupre, Nicole; Ge, Joy Yang; Bachman, Robert; Assaid, Christopher; Aurora, Sheena K; Michelson, David
Aim: The aim of this trial was to evaluate the efficacy and tolerability of ubrogepant (MK-1602), a calcitonin gene-related peptide receptor antagonist (CGRP-RA), for the acute treatment of migraine. Methods: This double-blind, placebo-controlled study randomized 834 participants to treat one migraine attack with ubrogepant 1 mg, 10 mg, 25 mg, 50 mg, 100 mg, or placebo in a 1:1 ratio. The co-primary endpoints were pain freedom and headache response at two hours. The first primary hypothesis tested the dose-response trend for two-hour pain freedom using a logistic regression model. Subsequent hypotheses tested the effects of each dose on the co-primary endpoints, using a closed sequential testing procedure to control for multiplicity. Results: A total of 527 participants received ubrogepant and 113 received placebo. A positive response trend in the proportion of participants achieving two-hour pain freedom was demonstrated ( p  < 0.001). Ubrogepant 100 mg was significantly superior to placebo for two-hour pain freedom (25.5% vs 8.9%) but not for two-hour headache response. Per the prespecified multiplicity strategy, this nonsignificant result precluded further formal hypothesis testing, although the 50 mg and 25 mg doses demonstrated nominal significance over placebo for two-hour pain freedom (unadjusted p  < 0.05). Overall, adverse events were similar between ubrogepant and placebo. Conclusion: This trial supports ubrogepant's efficacy and provides further evidence that CGRP-RAs are viable options for the acute treatment of migraine.